Homilies on Genesis and Exodus - Origen; Heine, Ronald E.; Origen (Washington, D.C. : Catholic University of America Press, 1982)
English translation made from the surviving Latin translation of Rufinus of Aquileia. Bibliography: p. vii-x. Includes indexes.
Homily VHomily VI -- Homily VII -- Homily VIII -- Homily IX -- Homily X -- Homily XI -- Homily XII -- Homily XIII -- Homily XIV -- Homily XV -- Homily XVI -- The Homilies on Exodus -- Homily I -- Homily II -- Homily III -- Homily IV -- Homily V -- Homily VI -- Homily VII -- Homily VIII -- Homily IX -- Homily X -- Homily XI -- Homily XII -- Homily XIII -- Appendix: The Interpretation of Names in the Genesis and Exodus Homilies -- Index of Proper Names -- Index of Holy Scripture
English translation made from the surviving Latin translation of Rufinus of Aquileia.
Includes bibliographical references (pages vii-x) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Bible. -- Sermons; Bible. -- Sermons; Bible. -- Sermons; Bible; Bible; Sermons, Latin -- Translations into English; RELIGION -- Biblical Studies -- Old Testament; RELIGION -- Sermons -- Christian; Sermons, Latin; Exodus (bijbelboek); Genesis (bijbelboek); sermons; Sermons; Translations; Preken (vorm); Sermons; Sermons